‘Let there be order!’: Rising criminal populism in Hungary: „Niech zapanuje porządek!”: Rosnący populizm penalny na Węgrzech (Archives of Criminology, 2023)
The article explains the birth and development of criminal populism in Hungary – a serious deficit of a young democracy since 2010. Ten years ago, the governing party Fidesz gained a two-thirds majority in the Parliament and immediately pushed penal policy reforms to the forefront of politics under the slogan ‘Order at last!’ The article describes the growing social and political tensions and the serious conflicts arising from the segregation of peripheries of society as a consequence of penal populism. Particular attention is paid to populist criminal policy regarding juveniles, which predominantly favours disciplinary measures. The scope of criminalised behaviour and punishable persons has been expanded; punishments are doled out and the prison population has increased considerably.